Estrategias para actuar en épocas de incertidumbre: una propuesta financiera (2020)
The economic cycles marked by a depression or recession in world economies, leads entrepreneurs and managers to implement strategies in their companies, to guarantee the growth and survival of their organizations, due to the difficulty in marking decisions under uncertainty. This document is intended to provide guidance to finance managers in the company, showing a framework that takes into account the strategy and the application of tools focused on obtaining liquidity, through the reactivation of businesses through innovation and creativity, to avoid a business bankruptcy. To build this framework that guides financial decisions in times of uncertainty, the document is built with an introduction to show the fundamentals of crises and the field of action of finance, a theoretical framework that serves as the basis for retaking the main contributions of economists such as Ezra Solomon, Zvi Bodie, Robert Merton, Tom Copeland, Oscar Leon García and from the strategic point of view Michael Porter, Henry Mintzberg, Robert Kaplan an David Norton, among others. The work plan that includes the initial diagnosis evaluating external and internal factors, the financial diagnosis, the application of financial tools, the participation of human talent in this situations of uncertainty and, finally, the conclusions highlighting the need to count is presented below with business strategies adapted through innovation and creativity, the participation of human talent in decision-marking and the construction of a management char with indicators that allow the finance manager to have a permanent X-ray of his company, with indicators that give an early warning.